Correction to: "Availability of healthcare providers for rural veterans eligible for purchased care under the veterans choice act" - Michael E. Ohl; Margaret Carrell; Andrew Thurman; Mark Vander Weg; Teresa Hudson; Michelle Mengeling; Mary Vaughan-Sarrazin (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.